Unraveling crimes with Geosciences - Roberta Somma (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2023)

(untitled)
The Forensic Sciences play an important and unique role in the Justice System, a role that refers to the expert’s ability to provide accurate and objective information reflecting facts and events that occurred during the happening of a crime. These sciences include Criminology and Criminalistics. Forensic Geology is a discipline, 150 years old, applied to criminalistics. It applies scientific principles of Earth Sciences to solve criminal cases. Main activities carried out by forensic geologists concern sedimentological, palaeontological, mineralogical, petrographic, and geochemical analyses, geophysical surveys, and remote sensing inspections. These investigations are used for solving crimes, such as homicides, corpse concealments, kidnappings, hit and run incidents, sexual assaults, counterterrorism, animal maltreating and wildlife crimes, robberies, thefts in apartments, vandalism, stone-throwings, frauds and financial crimes, and environmental damages. The present research illustrated the main activities carried out in Forensic Geology and selected some international and national cases carried out in the last 150 years by forensic geologists, for providing an overview of the scientific approaches, methods, and potentialities.